The role of prelamin A post-translational maturation in stress response and 53BP1 recruitment - Capanni, Cristina; Schena, Elisa; Di Giampietro, Maria Letizia; Montecucco, Alessandra; Mattioli, Elisabetta; Lattanzi, Giovanna (Frontiers in Cell and Developmental Biology, 2022)
Lamin A is a main constituent of the nuclear lamina and contributes to nuclear shaping, mechano-signaling transduction and gene regulation, thus affecting major cellular processes such as cell cycle progression and entry into senescence, cellular differentiation and stress response. The role of lamin A in stress response is particularly intriguing, yet not fully elucidated, and involves prelamin A post-translational processing. Here, we propose prelamin A as the tool that allows lamin A plasticity during oxidative stress response and permits timely 53BP1 recruitment to DNA damage foci. We show that while PCNA ubiquitination, p21 decrease and H2AX phosphorylation occur soon after stress induction in the absence of prelamin A, accumulation of non-farnesylated prelamin A follows and triggers recruitment of 53BP1 to lamin A/C complexes. Then, the following prelamin A processing steps causing transient accumulation of farnesylated prelamin A and maturation to lamin A reduce lamin A affinity for 53BP1 and favor its release and localization to DNA damage sites. Consistent with these observations, accumulation of prelamin A forms in cells under basal conditions impairs histone H2AX phosphorylation, PCNA ubiquitination and p21 degradation, thus affecting the early stages of stress response. As a whole, our results are consistent with a physiological function of prelamin A modulation during stress response aimed at timely recruitment/release of 53BP1 and other molecules required for DNA damage repair. In this context, it becomes more obvious how farnesylated prelamin A accumulation to toxic levels alters timing of DNA damage signaling and 53BP1 recruitment, thus contributing to cellular senescence and accelerated organismal aging as observed in progeroid laminopathies.